2005
DOI: 10.1098/rsif.2004.0028
|View full text |Cite
|
Sign up to set email alerts
|

Pathological pattern formation and cortical propagation of epileptic seizures

Abstract: The stochastic partial differential equations (SPDEs) stated by Steyn-Ross and co-workers constitute a model of mesoscopic electrical activity of the human cortex. A simplification in which spatial variation and stochastic input are neglected yields ordinary differential equations (ODEs), which are amenable to analysis by techniques of dynamical systems theory. Bifurcation diagrams are developed for the ODEs with increased subcortical excitation, showing that the model predicts oscillatory electrical activity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
104
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(108 citation statements)
references
References 34 publications
4
104
0
Order By: Relevance
“…Mean-field models have a long history in computational neuroscience (e.g., [26][27][28][29], including many important applications for seizure modeling. These include, for example, mean-field models of absence seizures (30)(31)(32), of depth and surface electrode recordings from patients with temporal lobe epilepsy (33,34), seizure generalization (35), and anesthetic-induced seizures (36).…”
Section: Signatures Of a Critical Transition In A Mean-field Model Ofmentioning
confidence: 99%
“…Mean-field models have a long history in computational neuroscience (e.g., [26][27][28][29], including many important applications for seizure modeling. These include, for example, mean-field models of absence seizures (30)(31)(32), of depth and surface electrode recordings from patients with temporal lobe epilepsy (33,34), seizure generalization (35), and anesthetic-induced seizures (36).…”
Section: Signatures Of a Critical Transition In A Mean-field Model Ofmentioning
confidence: 99%
“…There is also ambiguity in the lead/lag relationships determined by the Windowed Cross Correlation that they used. They suggested that the seizing activity of the cortex may be understood as an example of pathological pattern formation [14]. Kulish This paper attempts to suggest a phase-lagged model of single action potential which is based on fundamental laws of physics.…”
Section: Introductionmentioning
confidence: 99%
“…There have been several studies in associating cortical states (including seizures) measured in patients with these types of meso-scale cortical models and neural mass models for both seizures (Kramer et al 2005(Kramer et al , 2007NevadoHolgado et al 2012;Wang et al 2012;Aarabi and He 2014) and sleep (Lopour et al 2011;Dadok et al 2013). In Kramer et al (2005Kramer et al ( , 2007, pathways to seizure regions identified with bifurcation analysis through the particular mesoscale model used in this work were explored qualitatively to determine potential directions through seizure and enumerate seizure regions.…”
Section: Introductionmentioning
confidence: 98%
“…If we engineer a way to take EEG or ECoG measurements of seizures and learn how the corresponding physiology is changing in a model of the cortex, there is great potential to gain understanding of seizures that among other implications may in the future lead to new treatment strategies for individual seizures or epilepsy as a condition, including such options as new drug development to target certain physiological changes, new implantable therapies, or new algorithms for existing devices (Kramer et al 2005(Kramer et al , 2007Wendling 2008;Bazhenov et al 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation